Psychological Bias on Investment Decision Making Behaviour among Nepalese Investors - Bhattarai, Durga Maya; rana, Bikash (Devkota Journal of Interdisciplinary Studies, 2026)
This study investigates the impact of psychological biases on investment decision-making behaviour among Nepalese investors. Behavioural finance theories suggest that investors are often influenced by cognitive biases, leading to suboptimal financial decisions. This research aims to identify and assess the effects of key biases, including overconfidence, loss aversion, herding behaviour, recency bias, and self-attribution bias, on investment choices in Nepal.The study adopts a quantitative research design, utilizing a structured survey to collect data from 385 respondents. The data is analysed using statistical techniques such as descriptive analysis, correlation analysis, regression analysis, and hypothesis testing to determine the relationship between psychological biases and investment behaviour. The findings reveal that overconfidence bias, loss aversion, herding behaviour, and recency bias have a statistically significant impact on investment decision-making, whereas self-attribution bias does not exhibit a notable influence. Among these, herding behaviour has the strongest effect, indicating that Nepalese investors tend to rely heavily on market trends rather than independent decision-making. The results contribute to the field of behavioural finance by providing empirical evidence on how psychological biases shape investment behaviour. This study underscores the importance of financial literacy programs and investor awareness initiatives to mitigate the adverse effects of biases and encourage rational investment decisions. The findings also offer valuable insights for policymakers and financial institutions in designing investor friendly policies and educational interventions